Parental attachment, cognitive distortion, selfregulation and externalizing problem behavior among juvenile in rehabilitation institutions in Malaysia - Mohd Shakir, Athirah Yasmin (2019)
The present study aimed to examine a structural model on the relationship between parental attachment (i.e., paternal and maternal) and externalizing problem behavior (i.e., aggressive and rule-breaking), and the mediating effect of cognitive distortion. This study also examined whether the structural model is moderated by juvenile offenders’ self-regulation. A quantitative and cross-sectional approach was applied in the present study. This study was based on a large national research (Baharudin, Zulkefly & Arshat, 2015). A total of 440 juvenile offenders aged between 14 to 18 years old from all eight Juvenile Rehabilitation institutions or Tunas Bakti School (TBS), Malaysia were involved in this study. There were 268 males and 172 females who were identified via stratified random sampling technique. The Domain of Adolescent Attachment Scale- Malay (DAAS-Malay) (Zulkefly & Wilkinson, 2013), the Youth Self Report (YSR) (Achenbach, 1991), the 16-item version of ‘How I Think’ Questionnaire (HIT-16-Q) (Ara & Shah, 2015), and the Self-Regulation Scale (SRS) (Novak & Clayton, 2001) were utilized to assess the key variables of the study. The data were analyzed using the Statistical Package for Social Science (SPSS) and Analysis of Moment Structures (AMOS). The findings of the present study revealed that majority of juvenile offenders in the rehabilitation institutions reported high levels of aggressive and rulebreaking/ delinquent behavior as well as cognitive distortion. Whereas, the levels of paternal and maternal attachment and self-regulation among juvenile offenders were lower. Prior to the structural model testing, all of the key variables were validated with confirmatory factor analysis. The model indicated that both paternal and maternal attachment were significantly and negatively related to aggressive behavior; meanwhile, the respective relationship of paternal and maternal attachment with rule-breaking behavior was found to be insignificant. Moreover, the indirect effect indicated that the relationships of both paternal and maternal attachment with aggressive behavior were partially mediated by cognitive distortion. In contrast, the paths from paternal and maternal attachment to rule-breaking behavior were found to be completely mediated by cognitive distortion. Besides, the multi-group analysis found no significant moderation effect of juvenile offenders’ self-regulation on the model. This study concludes that parental attachment (i.e., paternal and maternal) and cognitive distortion possess protective effects against juvenile offenders’ externalizing problem behavior (i.e., aggressive and rule-breaking). The present findings imply that any effort to reduce juvenile offenders’ externalizing behavior should focus on the quality of parental attachment and cognitive distortion. Further, the findings presented in this study may contribute to the design of a more effective intervention program which aims to foster parental attachment and cognitive distortion to protect juveniles from engaging in externalizing problems.